Analysis of strategy of innovative activity of corporate engineering enterprises depending on the direction of impact factors on their activities - Круш, Наталія Петрівна (Technology audit and production reserves, 2016)
The features of the formation, implementation and improvement of strategy of innovative activity of corporate engineering enterprises are analyzed depending on the type of innovative behavior (leaders, followers, outsiders) and impact factors (demand for innovation, state government regulation of innovative activity and internal capacity of enterprises). Type of innovative behavior of corporate enterprise may change under the influence of these groups of factors and, in turn, will determine the need to clarify the strategic goals of innovative management. It is proved that the strategy of innovative activity of corporate engineering enterprises have developed, perfected and implemented under consideration of three-vector targeting of endogenous and exogenous environmental factors. It is determined that the factors of demand for innovation and state regulation of innovation currently do most destructive impact on the results of innovative management and corporate engineering enterprises leading to their strategic reorientation. It is identified that despite the inability or limited ability of corporate enterprises to influence environmental factors, they play an important role in stimulating innovative activity and state innovative strategy with appropriate differentiated approach could create incentives for each type of innovative enterprises. At the same time it is determined that the corporate enterprise may focusing now on the potential impact on key indicators that depend on them (internal potential) based on target approach and implementation of innovative audits that track mutual solution of strategic and tactical goals, the results of implementation and offer recommendations for its achievements in the case of deviations.